PSYCHOLOGICAL PERCEPTION OF A POLITICAL LEADER IN MODERN SOCIETY - Papoyan, Varduhi; Sargsyan , Hasmik (Modern Psychology, 2022)
The rapid changes of modern technologies, the process of perception move to another field, where the image of a political leader undergoes changes. According to that, the image of a political leader changes in the context of subjective perception. Often the political leader is perceived through myths, archetypes, myths, fairy tales, which shape the public perception, however, the political leader is perceived in the field of subjective perception, but includes elements of social perception. At present, the image of a political leader is formed through a number of mechanisms (PR technologies, advertisements), which complete the psychological portrait of the leader. Nowadays, modern technologies, new equipment և social platforms, create a new model of perception of a political leader, where  changes  not only the image of leader, but also  the  content. When we say change, we are talking about a new leader in the context of virtual reality, which is absolutely new, difficult to understand in the field of subjective perception of a person. The main function of the above-mentioned mechanisms is aimed at a clearer, more accessible perception of the political leader, which allows all layers of the society to form a certain image, by which the concept of leader will be more clearly perceived. However, it is necessary to study not only the mechanisms that contribute to changes in perception, but also to study and determine the main causes of these changes. The purpose of this article is to study and compare the psychological perception of the image of political leaders of the countries where transformations have taken place (Armenia, Russia, Belarus, USA) as well as explain the main reasons for the changes by ranking the characteristics of the image of a political leader. The research was conducted in two main stages. In the first stage, we studied the perception of the image of a political leader by non-specialists. We conducted a content analysis on the basis of which we singled out 10 qualities typical of a political leader. Then, in the second stage of the research, we examined the psychological perception of political leaders by political scientists through ranking.
Keywords: political leader; image; leader; perception; perception change